An introduction to management consultancy - Baaij, Marc G., 4 0 16; 5 (Los Angeles : SAGE, 2014)
u
Includes bibliographical references and index.
Adult.
Also issued online.
Keywords: 2 -- 0; 6; Business consultants; 20; 2